Critical analysis and review of the literature on healthcare privatization and its association with access to medical care in Saudi Arabia - Abdulwahab A. Alkhamis (Elsevier, 2017)
This paper is a review of the literature on hospitals privatization to assess the influence of privatization on access to medical care. The results are used to complete further analysis on the situation in Saudi Arabia. Over 979 references were initially identified through a database search, and an additional 237 were included from other sources. From these sources, only 11 articles were considered for review after excluding the ineligible articles, such as those that did not meet the hospitals privatization's definition or other exclusion criteria. There is weak evidence and low scientific validity supporting the argument that privatization could increase access to medical care. Prior to privatization, Saudi Arabia has to consider reforming its healthcare financing, including auditing and efficiency. After privatization, a policy has to be developed to ensure that the most vulnerable groups have access to good-quality healthcare while controlling costs for care providers. Keywords: Privatization, Hospital privatization, Healthcare conversion, Saudi health system